The Nonlinear Behavior of Ferrites at High Microwave Signal Levels - Suhl, Harry (Proceedings of the IRE, 1956)
Above a certain microwave signal level, ferrites show various kinds of anomalies in their power absorption. The conditions under which these anomalies are observed are shown to coincide with the conditions under which certain "spin wave" disturbances in the medium grow to abnormally high levels. This growth is caused by the coupling of the spin waves to the uniform precession through the demagnetizing and exchange fields that accompany the disturbances. In the first part of the paper it is shown that the coupling causes certain spin wave amplitudes to "run away" exponentially with time when the signal field exceeds a threshold value. This will happen most readily exactly at resonance and under suitable conditions in a range of dc biasing fields confined to the low side of resonance. In the second part, the steady state of the magnetization beyond the threshold signal is evaluated for one type of anomalous absorption. It is found that the uniform precession "saturates" at a value corresponding to the threshold signal, and that further increases in applied power are diverted into a narrow range of spin waves. The susceptibilities are computed in the new state. Agreement with experiment is found to be good throughout. Since the paper is intended to be tutorial in character, the analysis is kept to a minimum. The full analysis will be the subject of a later publication.